The Development of Personal Letter Material Through Flipbook to Enhance Students Reading Comprehension - Gianssi, Syerani Hestiza; Syahfutra, Wandi; Pahmi, Pahmi (ELT-Lectura, 2024)
In this sophisticated era, the learning process is very minimal using books. Most students are more interested in learning by using applications as learning media, because it is fun and not boring. One of the applications that can be used as learning media is the Flipbook application. This Flipbook application can enter data in the form of images, videos, music, keys, animations, and also links to other sources into one. Based on the researcher's experience while teaching, the researcher found the problem that occurred in students, namely the low interest in reading students in English lessons. This research was conducted to find out whether this Flipbook application can improve students' reading skills in English lessons about personal letters to 11th grade students of PGRI Pekanbaru High School. The researcher took samples in class XI IPS with a total of 32 students. After conducting the research, the researcher found an increase that has been seen from the t-test. The t-test score obtained is 29.62%, while the p-value is 0.000 <0.05. Based on the results of the research, it can be concluded that there is an increase in reading comprehension ability regarding personal letters in grade XI IPS of SMA PGRI Pekanbaru.